Rapid Detection of Hypervirulent Serovar 4h Listeria monocytogenes by Multiplex PCR - Feng, Youwei; Yao, Hao; Chen, Sisi; Sun, Xiaowen; Yin, Yuelan; Jiao, Xin’an (Frontiers in Microbiology, 2020)
Listeria monocytogenes (Lm) is a ubiquitous foodborne pathogen that comprises 14 serotypes, of which serovar 4h is a novel serotype recently reported. Serovar 4h L. monocytogenes belonging to hybrid sub-lineage II exhibit hypervirulent feature and they can’t be identified by conventional biochemical test or widely used PCR-based serogrouping scheme. In this study, we developed a new multiplex PCR assay for rapid detection of serotype 4h L. monocytogenes. Three primer pairs based on the target genes, LMxysn_1095, lmo1083, and smcL, were designed. The multiplex PCR results showed that serovar 4h strains could be specifically identified from all tested strains, including various L. monocytogenes serovars, Listeria spp. and other species. The detection limits of the multiplex PCR were 291 fg/ μL for genomic DNA and 5.5×106 CFU/ mL for bacterial suspension. Furthermore, raw pork meat artificially contaminated with serotype 4h L. monocytogenes in concentration of 1.8×103-1.8×100 CFU/ 10 g were successfully detected within 10-16 h. These results demonstrated that the multiplex PCR with high specificity and sensitivity, is applicable to detect L. monocytogenes serotype 4h strains rapidly.